The Development of Alveolar and Alveopalatal Fricatives in French-Speaking Monolingual and Bilingual Children. - Kehoe, Margaret; de Foy, Marie Philippart (Journal of Speech, Language & Hearing Research, 2023)
Purpose: This study conducted a transcription-based and spectral moments' analysis of alveolar and alveopalatal fricatives in monolingual and bilingual Frenchspeaking children, aged 2;6-6;10 (years;months). We measured the percent accuracy of fricatives and investigated whether young children could distinguish alveolar and alveopalatal fricatives on the basis of spectral moments. In addition, we examined which child- (i.e., age, gender, bilingualism, and alveopalatal fricative inventory size) and word/sound-related (i.e., place-of-articulation [PoA], voicing, vowel quality, and word position) factors influenced spectral moments and fricative duration. Method: Children (N = 89) participated in a picture-naming task in which they produced words containing alveolar /s, z/ and alveopalatal /ʃ, ʒ/ fricatives in word-initial, -medial, and -final positions. The words were transcribed and analyzed acoustically, and the first and third spectral moments (i.e., centroid and skewness) and the duration of fricatives were calculated. The data were subject to mixed-effects linear regression. Results: Percent accuracy results indicated effects of age on alveopalatal fricatives and effects of word position on voiced fricatives. Statistical models indicated that age, gender, and alveopalatal fricative inventory size influenced spectral moments. Age and inventory size interacted significantly with PoA. Children as young as age 2;6 distinguished alveopalatal and alveolar fricatives on the basis of centroid but not skewness values. The distinction between the two sets of fricatives increased with age. Bilingual children who spoke languages with greater numbers of alveopalatal fricatives distinguished alveopalatal and alveolar fricatives less well than monolinguals and bilinguals who spoke languages with fewer numbers of alveopalatal fricatives. Girls had higher centroid and lower skewness values than boys. Models also revealed a significant influence of word/sound-related factors (voicing, vowel quality, and word position) on spectral moments and fricative duration. Conclusions: Findings indicated that multiple factors influence the spectral moments and duration measures of children's alveolar and alveopalatal fricatives. In particular, we found that spectral moments were sensitive to gender and bilingualism effects.